An Examination of the Effects of Service Quality and Customer Satisfaction on Customer Loyalty in the Hotel Industry - Joko Sadoso Priyo; Bahtiar Mohamad; Raji Ridwan Adetunji (International Journal of Supply Chain Management, 2019)
This paper aims to investigate the direct and indirect effects of service quality and customer satisfaction on customer loyalty in the hotel service industry. It proposes to confirm a theoretical model which has not been identified in the literature within the spectrum of the hotel industry in Indonesia. A quantitative methodology was used in this study. 182 respondents of hotel customers in Indonesia were used to gather information about their perception of service quality, customer loyalty and satisfaction. PLS-SEM was used to analyse the collected data and to specify the Structural Equation Modelling (SEM) of the hypothesised model. The results revealed that SERVQUAL affects positively on customer satisfaction and customer loyalty. Similarly, the testing showed the positive effect of customer satisfaction on customer loyalty. A significant mediation effect of customer satisfaction was found on the relationship between SERVQUAL and customer loyalty. Therefore, the proposed model helps the hotel operator in developing their customer service development program to enhance customer’s satisfaction and loyalty to increase the profitability of the industry. This research contributes to hotel service industry by confirming the proposed structural model and offering insights about the customer perception, which helps hotel operators to more successfully incorporate the service quality to build customer loyalty and achieve customer satisfaction.